POETRY AND HUMOR IN SHEVCHENKO’S «JOURNAL» - Derzhavyn, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
First, after 1927, labor of Vladimir Derzhavyn (1899-1964) about the features of poetics and style of «Diary» of T. Shevchenko is published.